Linking Entrepreneurial Competence, Motivation, and Teacher Performance in Indonesian Vocational Education: A Structural Equation Modeling Analysis - Hastati, Sri; Wahid, Abdul; Afni, Nur (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This study examined the influence of principals' entrepreneurial competencies on teachers' motivation and performance in vocational high schools (SMKs) in Bulukumba Regency, using Covariance-Based Structural Equation Modeling (CB-SEM; AMOS v24). The structural model incorporated five dimensions of entrepreneurial competency (innovation, creativity, commitment, risk-taking, and team building), with teacher motivation as the mediating variable and teacher performance as the outcome. A sample of 200 teachers was drawn proportionally from 10 schools. Instrument validation confirmed high convergent validity and internal consistency (CRs 0.779–0.884; AVEs≥ 0.70). Model fit was evaluated using a contextual cross-index calibration approach, resulting in good fit indices (CFI = 0.989; RMSEA = 0.027; χ²(206) = 236.373, p = 0.072). Structurally, team-building (β = 0.404, p < 0.001), creativity (β = 0.165, p = 0.009), and commitment (β = 0.106, p = 0.042) showed significant direct effects on teacher performance, alongside teacher motivation (β = 0.291, p = 0.003). Motivation significantly mediated the impact of creativity on performance (t = 2.164). Collectively, this model explained 70.6% of the variance in motivation and 90.2% of the variance in performance. The novelty of this study lies in modeling the five dimensions of entrepreneurial leadership simultaneously, unlike previous research, which treated entrepreneurship as a unidimensional construct within a district-wide mediation framework. In practice, these findings suggest that leadership development programs should prioritize creativity, commitment, and team-building to enhance teacher motivation and performance in vocational education settings.